TSH−SPP1/TRβ−TSH positive feedback loop mediates fat deposition of hepatocyte: Crosstalk between thyroid and liver - Huang, Bin; Wen, Wenjie; Ye, Shandong (Frontiers in Immunology, 2022)
Background: It is well-known that thyroid hormone (TH) signaling have a significant effect on hepatic lipid metabolism. This study to determine whether TH receptor-beta (TRβ) function could be damaged by non-alcoholic fatty liver disease (NAFLD), thereby inducing thyroid hormone resistance-like manifestation and to analyze the potential role of SPP1 in the TH signaling pathway in the development of NAFLD. Methods: A total of 166 patients with BMI > 24 kg/m2 and were stratified into NAFLD and non-NAFLD groups. Age, sex and biochemical markers were obtained from the participants’ records. The dataset GSE48452 was downloaded and the Pathview library CIBERSORT algorithm was applied. Wild-type mice were divided into normal control (NC) and high-fat diet (HFD) groups. After 12 weeks, the obesity mice were sacrificed, and blood samples and livers were collected for subsequent molecular analyses. HepG2 cells and THP1 cells were treated with different concentrations of thyroid-stimulating hormone (TSH) and plasminogen activator for 24–72 h. In addition, a PC3.1-TRβ plasmid was constructed for use in HepG2 cells. Results: BMI, TSH, and free triiodothyronine (FT3) were significant independent risk factors of NAFLD. Further analysis with BMI stratification indicated that both FT3 and TSH had a significant change between those two groups in the obesity subgroup. Bioinformatics analysis of the GSE48452 dataset showed that several key molecules (including TRβ) of the thyroid hormone pathway were affected by NAFLD-induced transcriptomic changes. After 12 weeks of HFD feeding, Obesity mice had significantly high serum TSH and liver SPP1 levels, while TRβ was reduced. In vitro studies showed that SPP1 aggravated lipid deposition in hepatic cells depending on the downregulation of the expression of TRβ, and TSH acts to promote secretion of SPP1 in M1 macrophages. Conclusions: SPP1 secretion is induced by M1 macrophage polarization, which downregulates TRβ in hepatocytes in a paracrine manner. This causes lipid deposition to be aggravated in the liver and a compensatory increase in serum TSH levels that can further lead to SPP1 secretion by M1 macrophages. The positive feedback crosstalk between the thyroid and liver may play an important role in maintaining and amplifying the pathological process of NAFLD.